Association Between Sensory Profile and Daily Functioning in Children with Autism - Anindya, Isti; Soebandrio, Amin; Ariyanto, Ibnu Agus; Sekartini, Rini; Wiguna, Tjhin; Sari, Novika Purnama (Global Health Science Group, 2024)
In the diagnostic criteria outlined in the DSM-5-TR (APA, 2022) Autism is characterized by hyper- or hyporeactivity to sensory input or unusual interest. Children with Autism encounter challenges in processing sensory information, leading to difficulties in regulating responses to specific sensations and stimuli. Meanwhile, behaviours such as repetitive motor movements, running, aggression, and self-harming have been correlated with sensory processing disorders. Furthermore, some daily functioning that are often disrupted due to sensory processing disorders are sleeping, eating, and social activities. Therefore in this study, we aim to examine association between sensory profile and daily functioning in children with Autism. We collected data from parents of children aged 2-5 years with Autism (N = 96) and non Autism (N = 94) in Indonesia for three months (September-December 2023). Parents filled out five types of instruments (CARS-P, FISH, BAMBI, SCQ, and SSP) and sociodemographic data. The results of this study showed a significant difference between autistic and non-autistic groups in their daily functioning (p < 0.001). In autistic group, we found a significant relationship between sensory profiles and eating behavior (p < 0.001); and social communication skills (p < 0.001). In the non-autistic group, only sensory profile was corelated to eating behavior (p < 0.001). Primary results indicate that, the sensory profile is closely related to eating behavior and social communication skills in autistic children.